The Functional Visual Field(s) in simple visual search. - Wu, Chia-Chien; Wolfe, Jeremy M (Vision Research, 2022)
During a visual search for a target among distractors, observers do not fixate every location in the search array. Rather processing is thought to occur within a Functional Visual Field (FVF) surrounding each fixation. We argue that there are three questions that can be asked at each fixation and that these imply three different senses of the FVF. 1) Can I identify what is at location XY? This defines a resolution FVF. 2) To what shall I attend during this fixation? This defines an Attentional FVF. 3) Where should I fixate next? This defines an Exploratory FVF. We examine FVFs 2&3 using eye movements in visual search. In three Experiments, we collected eye movements during visual search for the target letter T among distractor letter Ls (Exps 1 and 3) or for a color X orientation conjunction (Exp 2). Saccades that do not go to the target can be used to define the Exploratory FVF. The saccade that goes to the target can be used to define the Attentional FVF since the target was probably covertly detected during the prior fixation. The Exploratory FVF is larger than the Attentional FVF for all three experiments. Interestingly, the probability that the next saccade would go to the target was always well below 1.0, even when the current fixation was close to the target and well within any reasonable estimate of the FVF. Measuring search-based Exploratory and Attentional FVFs sheds light on how we can miss clearly visible targets.